High‐pressure elasticity of serpentine and seismic properties of the hydrated mantle wedge. Issue 2 (20th February 2013) - Bezacier, L.; Reynard, B.; Cardon, H.; Montagnac, G.; Bass, J. D.
Abstract: [1] A subset of the single‐crystal elastic moduli of natural antigorite has been measured using Brillouin scattering at high‐pressure up to 9 GPa. Aggregate properties and axial compressibilities are in good agreement with equation‐of‐state results from X‐ray diffraction. Stiffness along the c ‐axis increases, becoming close to those within the silicate layer near 7 GPa. A slight discontinuity in the evolution of the elastic moduli near 7 GPa is associated with a phase transition. Raman spectroscopy shows that the transition does not occur in subducting slabs, except in the core of the coldest slabs where serpentine may be subducted to depths of about 200 km. Varying temperature and pressure has limited effects on the interpretation of seismic velocities, principally because of the limited depth range of serpentine stability (mostly above 100 km depth), and also due to the compensating effects of pressure and temperature that maintain velocity variations well within the uncertainties and statistical variability of seismological studies. Serpentinites are excellent candidates for explaining low velocities in the hydrated mantle wedge, inversion of the Moho, and thin anisotropic low‐velocity layers at the plate interface. Serpentinite layers provide an alternative explanation to fluid‐saturated oceanic crust for explaining these phenomena, and account for a transition to an aseismic, decoupled plate interface. Key Points: Elasticity of antigorite serpentine is measured at high pressures up to 9 GPa Serpentine can be detected as low seismic‐velocity areas down to 200 km depth Thin and deformed serpentine layers are detected at the subudction interface